How Venus Became Cool: Social and Moral Dimensions of Biosignature Science - Capper, Daniel (Zygon, 2021)
A 2020 scientific report indicated the presence of phosphine, a potential biosignature chemical, in the atmosphere of Venus. As a result, Venus instantly became a global cultural celebrity. How did Venus become so fashionable, so cool in colloquial language, so quickly? I contend that Venus became the center of attention at least temporarily because Venus became moral. Since life at present is a concept that is as much moral as it is scientific, I explain this point by offering a geographically broad sampling of world philosophies that show that secular and religious Western forms of thought strongly value life over nonlife as do many Asian traditions. These cultural valuations of life over nonlife become infused in human psychologies globally and astonish us at the discovery of extraterrestrial life. This essay's substantial culture sample thereby demonstrates that Venus became revered because of deep-seated but also widespread attitudes of special moral attendance to the presence of life especially in extraterrestrial settings.